2012
DOI: 10.1179/1351000212y.0000000021
|View full text |Cite
|
Sign up to set email alerts
|

The expression of thioredoxin-1 in preterm delivery placenta

Abstract: These results indicate that TRX-1 may be adaptively induced by the effects of inflammation and oxidative stress, suggesting protective roles for TRX-1 against these effects in the placenta of PTD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…In one study that we reviewed, researchers reported higher TRX-1 mRNA and protein levels in PTB placental tissue compared to TB placental tissue, suggesting that dysregulation of the Trx system within the placenta may be associated with PTB (Song et al, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…In one study that we reviewed, researchers reported higher TRX-1 mRNA and protein levels in PTB placental tissue compared to TB placental tissue, suggesting that dysregulation of the Trx system within the placenta may be associated with PTB (Song et al, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…This oxidative stress occurs in hypoxia circumstances. (Dong et al, 2012) Study by Dong et al found that there was a significantly increased HIF-1α mRNA level in premature placenta compared with term placenta. This increased expression of HIF-1α may be related to oxidative stress condition in the premature placenta.…”
Section: Ethical Clearancementioning
confidence: 99%
“…In the development of early pregnancy, hypoxia condition is needed for the process of cytotrophoblasts invasion and infiltration into the decidua, to maintain the feto-maternal circulation.Therefore, HIF-1α will be expressed in the early trimester placenta and decreased with the increasing gestational age. (Dong et al, 2012;Rath et al, 2016)However, if the hypoxia continues until the final trimester, it can cause pain and even death for both mother and fetus. (Rath et al, 2016)Hypoxic placenta releases several mediators into the maternal circulation, one of which plays an important role is HIF-1α, a transcription factor for oxygen-dependent genes, to express proteins related to cell metabolism and angiogenesis.…”
Section: Ethical Clearancementioning
confidence: 99%
See 2 more Smart Citations